The materiality and efficacy of Balinese letters: situating scriptural practices - Fox, Richard Gabriel; Hornbacher, Annette (Brill's Southeast Asian library, 2016)
The Materiality and Efficacy of Balinese Letters' examines traditional uses of writing on the Indonesian island of Bali, focusing on the power attributed to Balinese script. The approach is interdisciplinary and comparative, bringing together insights from anthropological and philological perspectives. Scholars have long recognized a gap between the practices of philological interpretation and those of the Javano-Balinese textual tradition. The question is what impact this gap should have on our conception of 'the text'. Of what relevance, for example, are the uses to which Balinese script has been put in the context of ceremonial rites? What ideas of materiality, power and agency are at work in the production and preservation of palm-leaf manuscripts, inscribed amulets and other script-bearing instruments?
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Electronic books -- Electronic books; Konferenzschrift; Ritus; Alphabet; Schriftzeichen; Balinesisch